Flowering and seed production of sandalwood (Santalum album; Santalaceae) along environmental gradients in Gunung Sewu Geopark, Indonesia - YENI W.N. RATNANINGRUM; ENY FARIDAH; SAPTO INDRIOKO; ATUS SYAHBUDIN (Nusantara Bioscience, 2016)
Abstract. Ratnaningrum YWN, Faridah E. Indroko S, Syahbudin A. 2016. Flowering and seed production of sandalwood (Santalum album; Santalaceae) along environmental gradients in Gunung Sewu Geopark, Indonesia. Nusantara Bioscience 8: 180-191. We observed flowering and seed production of sandalwood populations along environmental gradients in Gunung Sewu Geopark, Indonesia, in 2013 to 2014 flowering periods. We observe flowering phenology with regard to floral initiation, phases and periods, and measured Pollination Effectiveness and Reproductive Success, following modified methods of Owens et al and Ghazoul. Flowering and seed production varied with altitude and climatic conditions, and altered by changes in rainfall, temperature and soil moisture. Sites with lower altitude, lower rainfall, highest temperature, lowest relative humidity, and lowest soil moisture flowered earlier and shorter. Flowering delayed and prolonged by increasing altitude, temperature, and humidity. At all sites, ?owering delayed and prolonged in rainy compared to dry season. Lower populations produced more flowers in rainy season, however, higher abortion resulted in very low seed production. Dry season produced less flowers but higher reproductive success was achieved, resulting in more fruits. The lowest altitude performed highest reproductive outputs. More marked differences among sites were observed in the dry season. Flowering and seed production was also observed to be temperature sensitive. Both drop and increase on temperature resulted in the alteration of flowering frequency and reproductive outputs. Sandalwood in Gunung Sewu grows naturally in association with tropical monsoon vegetation, i.e. acacia, cajuputi, teak, and mahogany. The conservation of this endangered species, particularly under wider range of landscapes, should be maintained with a different strategy according to the degree of plant sensitivity to environmental features.